2010
DOI: 10.1177/0269215510375907
|View full text |Cite
|
Sign up to set email alerts
|

The role of religiosity, coping strategies, self-efficacy and personality dimensions in the prediction of Iranian undergraduate rehabilitation interns’ satisfaction with their clinical experience

Abstract: religiosity, problem-focused coping and general self-efficacy seem to be good predictors of satisfaction with clinical internship in rehabilitation students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
(38 reference statements)
3
22
3
1
Order By: Relevance
“…In view of this, it appears that having religious beliefs enables rehabilitation experts to consider helping patients as a way of finding the meaning of life and gaining a higher job satisfaction. This finding was consistent with previous studies [3,4,[23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In view of this, it appears that having religious beliefs enables rehabilitation experts to consider helping patients as a way of finding the meaning of life and gaining a higher job satisfaction. This finding was consistent with previous studies [3,4,[23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 94%
“…Correlation and regression analysis of religious beliefs, faith at work, and spirituality to predict job satisfaction of rehabilitation experts. may have higher levels of job satisfaction [3,4]. Studies have shown that people may use religion as a defense mechanism to cope with educational or job-related problems [33] and find meaning in their jobs, which lead them to obtain greater job satisfaction [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Chibnall et al (2009) showed that extraversion and openness influence self development, leadership and problem solving among medical students. Results of a study by Mirsaleh et al (2010) showed that there was positive correlation between openness and conscientiousness and negative correlation between neuroticism and satisfaction with clinical training.…”
Section: Introductionmentioning
confidence: 99%